Diminished lung function, RSV infection, and respiratory morbidity in prematurely born infants. Issue 1 (27th September 2005) - Broughton, S; Bhat, R; Roberts, A; Zuckerman, M; Rafferty, G; Greenough, A
Abstract : Background: Diminished lung function appears to be a risk factor for respiratory syncytial virus (RSV) infection/bronchiolitis in term born infants. Aims: To determine if diminished lung function prior to neonatal unit discharge was associated with subsequent symptomatic RSV lower respiratory tract infection (LRTI) and respiratory morbidity in prematurely born infants. Methods: Of 39 infants in a tertiary neonatal intensive care unit (median gestational age 28 weeks, range 23–31), 20 had bronchopulmonary dysplasia. Lung function (compliance and resistance of the respiratory system (Crs and Rrs ) and functional residual capacity (FRC)) was measured on the neonatal unit at 36 weeks postmenstrual age (PMA). Following neonatal unit discharge, nasopharyngeal aspirates were obtained on every occasion, at home or in hospital, an infant had an LRTI. RSV was identified by immunofluorescence and/or culture. Results: The 15 infants who suffered a symptomatic RSV LRTI had a higher mean Rrs and suffered more wheeze at follow up than the rest of the cohort. Regression analysis showed that a high Rrs was significantly associated with a symptomatic RSV LRTI; significant factors for cough were a high Rrs and a symptomatic RSV LRTI, and for wheeze were a high Rrs . Conclusion: Prematurely born infants, who had a symptomatic RSV LRTI and/or respiratory morbidity at follow up, had worse lung function prior to neonatal unit discharge.